Hukum perdata internasional Indonesia - S. Gautama (Alumni, 1973)
tr, jil.1=c.1-3 ; jil.2[bag.2]=c.1 ; jil.2 [bag.3]=c.1-2 ; jil.2 [bag.4]=c.1 ; jil.2 [bag.5]=c.1/why, jil. 1=c.4/tr, jil.2 [bag.2]=c.2